Glioblastoma Multiforme: an Advanced Analysis of 153 Patients and Review of the Literature - Nikdad, Mohammad Sadegh; Farhan, Farshid; Shafizadeh, Milad; Mirmohseni, Atefeh Sadat; Afarideh, Mohsen; Komeleh, Shabnam Asadi; Lashkari, Marzieh; Ganji, Morsaleh; Ghajar, Alireza; Shafiei, Saeed; Shafizadeh, Yalda; Kazemian, Ali; Saberi, Hooshang (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Objective Glioblastoma multiforme (GBM) is an aggressive primary tumor with frequent recurrences that leaves patients with a short survival time and a low quality of life. The aim of this study was to review the prognostic factors in patients with glioblastoma multiforme.Material and Methods The focus of this retrospective study was a group of 153 patients with supratentorial GBM tumors, who were admitted to a tertiary-care referral academic center from 2005 to 2013. The factors associated with survival and local recurrence were assessed using the hazard ratio (HR) function of Cox proportional hazards regression and neural network analysis.Results Out of the 153 patients, 99 (64.7%) were male. The average age of the patients was 55.69 ± 15.10 years. The median overall survival (OS) and progression-free survival (PFS) rates were 14.0 and 7.10 months respectively. In the multivariate analysis, age (HR = 2.939, p < 0.001), operative method (HR = 7.416, p < 0.001), temozolomide (TMZ, HR = 11.723, p < 0.001), lomustine (CCNU, HR = 8.139, p < 0.001), occipital lobe involvement (HR = 3.088, p < 0.001) and Karnofsky Performance Status (KPS, HR = 4.831, p < 0.001) scores were shown to be significantly associated with a higher OS rate. Furthermore, higher KPS (HR = 7.292, p < 0.001) readings, the operative method (HR = 0.493, p = 0.005), the use of CCNU (HR = 2.047, p = 0.003) and resection versus chemotherapy (HR = 0.171, p < 0.001) were the significant factors associated with the local recurrence of the tumor.Conclusion Our findings suggest that the use of CCNU and TMZ, the operative method and higher KPS readings are associated with both higher survival and lower local recurrence rates.
Keywords: glioblastoma multiforme; survival; local recurrence